A Note on the Normal Index and the c-Section of Maximal Subgroups of a Finite Group - Na Tang; Xianhua Li (Journal of Applied Mathematics)
Let M be a maximal subgroup of finite group G. For each chief factor H/K of G such that K≤M and G=MH, we called the order of H/K the normal index of M and M∩H/K a section of M in G. Using the concepts of normal index and c-section, we obtain some new characterizations of p-solvable, 2-supersolvable, and p-nilpotent.